Population Density and Fertility in Farm Households: A Study of the Millennium Development Authority Zones in Ghana - Ahiadeke, C.; Der, D.D. (Environment, Development and Sustainability, 2013)
Agriculture is mainly a rural preoccupation, and about three quarters of the population growth in developing countries emanate from agricultural households. Some demographers posit that the agricultural system affects birth rates; in addition, population pressures might put stress on agricultural land in farming communities. This paper focuses on the population to land ratio in the Millennium Development Authority (MiDA) Enumeration Areas (EAs) in Ghana and tackles the important question: Do households adjust to an increasing population/land ratio by having fewer children? The authors explore this theme in the context of rural population density and fertility in the three MiDA zones, drawing on data collected in 23 EAs in Ghana in 2008. The results suggest that fertility in the MiDA zones can be affected by density if nothing is done to regulate population density. The regression estimates for the pooled data show that all the coefficients are negative and statistically significant at the 0.05 level or better. Thus, children ever born is inversely correlated with density, agricultural production, female literacy and the trend variable (year). The estimates from the cross-sectional data as well as the spatial coefficient were consistent with those of the pooled data. The results under various model specifications are stable. We find from the Cox model that areas with higher education levels and a lower share of individuals working in agriculture, both correlated with land use. Agricultural production has at most a modest independent effect on fertility. Our findings suggest that population density has a reasonable inhibiting effect on fertility in the MiDA Zones. © 2012 Springer Science+Business Media Dordrecht.
Keywords: Agriculture; Farming; Fertility; Households; Land; Population density